Camel milk inhibits pulmonary oxidative stress and inflammation in a rat model of COPD induced by cigarette smoke exposure - Sepide Behrouz; Mahla Mohammadi; Hadi Sarir; Nema Mohammadian Roshan; Mohammad Hossein Boskabady (Heliyon)
Background: One of the main causes of death in the world is chronic obstructive pulmonary disease (COPD) with partially reversible airflow limitation, which is defined as a preventable and treatable pathological condition. Anti-inflammatory and antioxidant properties of camel milk (CM) were indicated previously. The effect of CM in cigarette smoke induced-COPD in rats was evaluated in this study. Methods: Five groups of rats including a) control, b) chronic obstructive pulmonary diseases (COPD, cigarette smoke exposed), c) COPD group treated with dexamethasone, d) COPD group treated with low dose of camel milk (CM) and e) COPD group treated with high dose of CM by gavage during the cigarette smoke exposure period (n = 7) were studied. Results: In the COPD group, total and differential white blood cells (WBC) count in the bronchoalveolar fluid (BALF), tumor necrosis factor-alpha (TNF-α) level in the lung tissue and malondialdehyde (MDA) level in the BALF and lung tissue, lung pathological changes and tracheal responsiveness to methacholine were significantly increased, but catalase (CAT) and superoxide dismutase (SOD) activities and the level of thiol in the BALF and lung tissue were significantly decreased compared to the control group (all, p < 0.001). However, in the COPD groups treated with both doses of CM and dexamethasone, most variable did not achieved to the control levels and were significantly different with the control group (p < 0.05 to p < 0.001). In the COPD group treated with both doses of CM (dose dependently) and dexamethasone, almost all measured variables were significantly improved (p < 0.05 to p < 0.001). Conclusion: The potential effect of CM on lung inflammation and oxidative stress in a rat model of COPD comparable to dexamethasone was demonstrated.